2015
DOI: 10.1371/journal.pone.0141054
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Heat on an Emergency Department in Italy: Attributable Visits among Children, Adults, and the Elderly during the Warm Season

Abstract: IntroductionRecent studies suggest that heat is associated with an increase in the number of ambulance calls and emergency department visits. We investigated the association between heat and daily number of emergency department visits at the University Hospital of Verona during the warm seasons 2011–2012 and we assessed the magnitude of the impact in terms of attributable events, focusing on the role of age and triage codification.Materials and methodsWe used a Poisson model to analyse the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Here, we build upon previous work in Atlanta in which, similar to studies in other regions ( Basu et al 2012 ; Ghirardi et al 2015 ; Petitte et al 2016 ; Saha et al 2015 ), we observed associations between continuous maximum temperature and maximum apparent temperature and ED visits for all internal causes, heat illness, fluid/electrolyte imbalances, renal diseases, asthma/wheeze, diabetes, and intestinal infections ( Winquist et al 2016 ). For the present study, we were specifically interested in the added effect of extreme heat over a sustained period beyond the continuous temperature–response relationships.…”
Section: Introductionmentioning
confidence: 56%
“…Here, we build upon previous work in Atlanta in which, similar to studies in other regions ( Basu et al 2012 ; Ghirardi et al 2015 ; Petitte et al 2016 ; Saha et al 2015 ), we observed associations between continuous maximum temperature and maximum apparent temperature and ED visits for all internal causes, heat illness, fluid/electrolyte imbalances, renal diseases, asthma/wheeze, diabetes, and intestinal infections ( Winquist et al 2016 ). For the present study, we were specifically interested in the added effect of extreme heat over a sustained period beyond the continuous temperature–response relationships.…”
Section: Introductionmentioning
confidence: 56%
“…Previous studies of deaths and consultation numbers associated with heat-related diseases have reported that death or the risk of death increases[ 29 30 31 ] and that the number of patients visiting hospitals[ 32 ] or calling for emergency services[ 16 ] increases when the temperature exceeds a certain threshold. Even a 1.5°C increase above the mean daily maximum temperature (75 th percentile) increases demand for emergency transportation due to heat-related diseases by 2.4–8.9 times.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also highlight an increase in emergency department visits by children in urban areas during heatwaves (Ghirardi et al, 2015;Sheffield et al, 2018;van der Linden et al, 2019). Asthma and other respiratory diseases are the most common associated health conditions among children and infants.…”
Section: Natural Hazards and Children's Healthmentioning
confidence: 99%